Pengaruh Motivasi terhadap Kinerja Perawat di Rumah Sakit: The Effect of Motivation on Nurse Performance in the Hospital - Azzilla Nur Layli; Chriswardani Suryawati; Wulan Kusumastuti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Content Nurses are one of the professions that have the most human resources in hospitals which is 50% and has an important role in the provision of health services. A work boost is needed in hopes of improving and delivering optimal performance. Providing work motivation is a way to improve performance in nurses and encourage to carry out activities in order to achieve their goals and to meet their needs. Without motivation, the task carried out will not be carried out according to the standards because what has become his motive and motivation in working is not fulfilled. From 10 motivational variables, found 9 variables that can affect the performance of nurses in the hospital include achievement, self-employment, responsibility, development of individual potential, policy and administration, incentives/salaries, working relationships, working conditions, and quality of supervision. Incentive/salary variables are more dominant to influence motivation towards hospital nurse performance. Keywords: Motivation, Job Performance, Nurse Abstrak Perawat adalah salah satu profesi yang memiliki sumber daya manusia paling besar di rumah sakit yaitu sebesar 50% dan memiliki peranan penting dalam pemberian pelayanan kesehatan. Dorongan kerja sangat diperlukan dengan harapan dapat meningkatkan dan mewujudkan kinerja yang optimal. Memberikan motivasi kerja merupakan cara untuk meningkatkan kinerja pada perawat serta mendorong untuk melaksanakan kegiatan agar mencapai tujuan serta dapat memenuhih kebutuhannya. Tanpa motivasi, tugas yang dilaksanakan tidak akan dijalani sesuai standar sebab apa yang telah menjadi motif dan motivasinya dalam bekerja tidak terpenuhi. Dari 10 variabel motivasi, ditemukan bahwa 9 variabel mempengaruhi kinerja perawat di rumah sakit diantaranya adalah prestasi, pekerjaan itu sediri, tanggung jawab, pengembangan potensi individu, kebijakan dan administrasi, insentif/gaji, hubungan kerja, kondisi kerja, dan kualitas supervisi. Variabel insentif/gaji lebih dominan untuk mempengaruhi motivasi terhadap kinerja perawat. Kata Kunci: Motivasi, Kinerja, Perawat